Logan [videorecording (Blu-Ray)] - Mangold, James; Frank, Scott, 1960-; Green, Michael (Screenwriter); Jackman, Hugh; Stewart, Patrick, 1940-; Holbrook, Boyd, 1981-; Merchant, Stephen; Grant, Richard E., 1957-; La Salle, Eriq, 1962-; Neal, Elise, 1970-; Rodriguez, Elizabeth, 1980-; Keen, Dafne; et al. (20th Century Fox Home Entertainment, 2017)
In 2029, a weary Logan earns a living as a chauffeur while caring for the ailing Professor X in a hideout on the Mexican border. But Logan's attempts to escape from the world and his legacy are upended when a young mutant girl with extraordinary fighting prowess requires his help to outrun sinister figures working for a powerful corporation.